The Effect of Service Quality and Tax Knowledge on the Satisfaction of Taxpayers of Personal Persons (Case Study at Kpp Pratama Medan Timur) - Fitri Handayani; Candy Lie (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine how the effect of service quality and tax knowledge on individual taxpayer satisfaction at KPP Pratama Medan Timur. The research method that will be used is descriptive quantitative, while the data collection method used is a questionnaire which will then be measured with a Likert scale. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially or simultaneously the variables of service quality and tax knowledge have a significant influence on individual taxpayer satisfaction at KPP Pratama Medan Timur.